Japan, the culture - Kalman, Bobbie (New York : Crabtree, 2001)
Discusses the culture of the Japanese people, introducing the mythology, crafts, foods, festivals and more.
Includes index.
SLJ
AR
VOYA
6.6.
3-7.
Keywords: Japan -- Civilization; Japan -- Social life and customs